1988
DOI: 10.1161/01.str.19.10.1216
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial thrombolytic therapy improves outcome in patients with acute vertebrobasilar occlusive disease.

Abstract: In this retrospective analysis we report our treatment experience in 65 consecutive patients with clinical signs of severe brainstem ischemia with angiographically demonstrated thrombotic vertebrobasilar artery occlusions who received either local intra-arterial thrombolytic therapy (urokinase or streptokinase) (43 patients) or conventional therapy (antiplatelet agents or anticoagulants) (22 patients). We analyzed the data with respect to cerebral artery occlusion patterns, posttreatment arterial recanalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
379
2
33

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 744 publications
(428 citation statements)
references
References 38 publications
14
379
2
33
Order By: Relevance
“…To our best knowledge, systematic data on safety of MT devices comparing different generations of recanalization devices and techniques are not available yet. In our study, reflecting ''real-world'' experience, we could show that modern stent retriever and suction thrombectomy In previous studies on intra-arterial fibrinolysis, recanalization rates of approximately 50-60 % for complete recanalization, and B70 % when combining partial and complete recanalization, were reported in acute BAO [1][2][3][4][5][6]. Until now, only anecdotal reports and small singlecenter studies on MT in BAO have reported promising recanalization rates of 72-100 % [7,11,17,18].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…To our best knowledge, systematic data on safety of MT devices comparing different generations of recanalization devices and techniques are not available yet. In our study, reflecting ''real-world'' experience, we could show that modern stent retriever and suction thrombectomy In previous studies on intra-arterial fibrinolysis, recanalization rates of approximately 50-60 % for complete recanalization, and B70 % when combining partial and complete recanalization, were reported in acute BAO [1][2][3][4][5][6]. Until now, only anecdotal reports and small singlecenter studies on MT in BAO have reported promising recanalization rates of 72-100 % [7,11,17,18].…”
Section: Discussionsupporting
confidence: 70%
“…Although the standard therapy, local intra-arterial fibrinolysis, has decreased mortality rates in acute true basilar artery occlusion (BAO) from 80 to 90 % to approximately 60 %, acute basilar artery embolism is still a devastating life-threatening disease [1][2][3][4]. Furthermore, intra-arterial fibrinolysis has some limitations (e.g., low efficiency in cases of large thrombus load, frequent distal embolization, extensive time to recanalization) and potential intrinsic complications (i.e., intracranial bleeding) [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with a mortality between 50% and 90% in patients treated conventionally (antiplatelets or heparin) or not at all. 2,3 If survived, the consequence frequently is a locked-in syndrome, the most gruelsome outcome thinkable. Different patterns include caudal vertebrobasilar, mid-basilar and top-of-the-basilar thrombosis, the former mostly being of atherothrombotic and the latter of embolic origin.…”
Section: B Asilar Artery Thrombosis (Bat) Is a Rare But Mostmentioning
confidence: 99%
“…6,7 Most studies suffered from small numbers: Ͻ10 patients with only a few in the range of 40 to 50 patients. 2,8,9 All had an open, retrospective or partly prospective design with differing treatment regimens, mostly IA thrombolytic drugs formally rendering level III evidence at best.…”
Section: B Asilar Artery Thrombosis (Bat) Is a Rare But Mostmentioning
confidence: 99%